Impact of ecology-based nature education on the behavior of secondary school students
Urbanization decreased natural habitats and technological developments cause children to become more and more disconnected from nature (Kahyaoğlu & Yetişir, 2015). This disconnection has increased interest in ecology-based nature education in many countries. Ecology-based nature education is an out-of-school education program that enables to develop awareness of nature and environment in individuals, protect living and inanimate beings in nature, and better understand human-nature relations. It covers a wide range of people from preschool, primary, secondary, undergraduate, graduate and teachers. Accordingly, it is seen that there has been an increase in studies on ecology-based nature education in recent years (Keçeci, Kırbağ-Zengin & Alan, 2019; Özgel, Aydoğdu & Yıldırım, 2018; Kınık-Topalsan, Türk & Güler, 2019; Temiz & Karaarslan-Semiz, 2019). However, when the articles on this field are examined, it is seen that the studies on the role and effect of ecology-based nature education on the behavior of students connecting to nature are not enough. The aim of this research is to examine the impact of ecology-based nature education on the behavior of secondary school students towards nature within the framework of Bowlby’s theory of attachment and to present their views on ecology-based nature education applied. In this context, the research was carried out with a mixed method research pattern. The working group of the study consists of 40 students, who participated in the training with the principle of volunteerism, in a province located in Southeastern Anatolia Region of Turkey. All activities of this training were carried out within the borders of the province. Quantitative data of the study were obtained by “Nature Commitment Scale” and qualitative data were obtained by semi-structured interview form. Quantitative data of the study were analyzed by independently related sample t-test and qualitative data were analyzed by content analysis. In the study, it was determined that ecology-based nature education had a statistically significant effect on the connection behavior of secondary school students to nature. In addition, it was determined that secondary school students who participated in ecology-based nature education with some expectations such as, raising awareness, doing activities, gaining experience and communicating. After the training, it was determined that the expectations of the students were met.

(untitled) - Kahyaoğlu, Mustafa; Karakaya-Bilen, Ebru; Saraçoğlu, Mehtap (European Journal of Education Studies, 2021)
Keywords: bonding; ecology-based nature education; nature; secondary students